Respuesta :

Answer:

Option (3)

Step-by-step explanation:

Given expression represents the sum of k terms of a geometric sequence.

[tex]\sum_{k=1}^{9}2(4)^{k-1}[/tex]

Since, formula to calculate the sum of a geometric sequence is given by,

[tex]\sum_{n=1}^{n}a(r)^{n-1}=\frac{a(1-r^n)}{1-r}[/tex]

By this formula,sum of 9 terms of the given sequence will be,

[tex]\sum_{k=1}^{9}2(4)^{k-1}=\frac{2(1-4^9)}{1-4}[/tex]

Therefore, Option (3) will be the answer.

Answer:

Thank you for your service! This was super helpful.

Step-by-step explanation:

(: